Epilepsy surgery of focal cortical dysplasia–associated tumors. (December 2013) - Cossu, Massimo; Fuschillo, Dalila; Bramerio, Manuela; Galli, Carlo; Gozzo, Francesca; Pelliccia, Veronica; Casaceli, Giuseppe; Tassi, Laura; Lo Russo, Giorgio
Summary: The goal of the present study was to evaluate the clinical characteristics and postoperative seizure outcome of epileptogenic tumors associated with focal cortical dysplasias (FCDs) compared to both solitary FCD type I and solitary tumors. Particular attention is given to FCD type IIIb (tumors associated with FCD type I), which have been recently classified as a separate entity. We retrospectively reviewed the clinical charts of 1, 109 patients who were operated on for drug‐resistant focal epilepsy, including 492 patients with a histologic diagnosis of solitary FCD I and II (83 and 157 cases, respectively), solitary tumors (179 cases), and FCD‐associated tumors (73 cases, 58 of which met the criteria of FCD IIIb of the new International League Against Epilepsy [ILAE] classification). The different subgroups were evaluated for clinical characteristics and postoperative surgical outcome. Clinical variables and postoperative seizure outcome of patients with coexisting tumor and FCDs (FCD IIIb and tumor associated FCD II) were similar to those of patients with a solitary tumor and differed significantly from patients with solitary FCDs. Nevertheless, tumors associated with FCDs are characterized by a striking male predominance and a higher seizure frequency as compared to solitary tumors. Patients with drug‐resistant focal epilepsy secondary to a solitary tumor or with a tumor‐associated FCD have similar basic clinical presentation and postoperative seizure outcome. Nevertheless, the epileptogenic contribution of the associated FCDs can be crucial, and it needs to be adequately assessed. The impact of FCD on tumor‐related epilepsy deserves future research in order to optimize the surgical strategies aimed at seizure relief.